Reverse effects of Streptococcus mutans physiological states on neutrophil extracellular traps formation as a strategy to escape neutrophil killing - Huang, Lijia; Lu, Wenhua; Ning, Yang; Liu, Jia (Frontiers in Cellular and Infection Microbiology, 2022)
Bacteria in nature are present in different lifestyles with distinct characteristics. Streptococcus mutans is the etiologic pathogen of dental caries and could easily gain access into the bloodstream after oral surgery and adopt a biofilm lifestyle, resulting in infective endocarditis. A growing amount of evidence have revealed that the large web-like structure composed of extracellular DNA and antimicrobial proteins released by neutrophils, named Neutrophil Extracellular Traps (NETs), play an active role in the defense against bacterial invasion. The present study demonstrated that NETs formation was discriminatively affected by S. mutans biofilm and its planktonic counterpart. The free-floating planktonic S. mutans exhibited an active NETs response, whereas the biofilm community exhibited a reverse negative NETs response. Besides, impaired biofilm killing correlated with the decrease in NETs production. Unlike planktonic cells, biofilm avoided the burst of reactive oxygen species (ROS) when co-culture with neutrophils, and the NADPH-oxidase pathway was partially involved. A mice infection model also supported the distinguishing response of neutrophils challenged by different lifestyles of S. mutans. In conclusion, different bacterial physiological states can affect the distinct response of the host–microbe interaction, thus contributing to the anti-pathogen immune response activation and immune surveillance survival.